Bladder Irrigation with 1% Povidone-Iodine Reduces Catheter Associated Urinary Tract Infections in ICU Patients (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Objective: Urinary tract infections (UTI) are commonly acquired in hospitals, within an estimated prevalence of 1% -10% representing 30%-40% of all nosocomial infections. The most important risk factor for the development of nosocomial UTI, especially in the ICU is the presence of urinary catheter. Catheter related urinary tract infection occurs because urethral catheters inoculate organisms into the bladder and promote colonization by providing surface for bacterial adhesion and causing mucosal irritation. This study was performed to determine the effectiveness of 1% povidone-iodine bladder wash in the prevention of catheter-associated urinary tract infection (CAUTI) in ICU patients.Methodology: This experimental study was carried out during a period of two years. A total of 80 admitted patients who need Foley's catheter in ICU during this study period at the study place were included in the study. Patients were enrolled in two groups by purposive sampling. Group-A; received 1% povidone-iodine bladder wash, Group-B: received standard catheter care. Tri-channel Foley's catheter was introduced with standard aseptic protocol and patient who received Bi-channel Foley's catheter at operation theater on same ICU admission day, the catheter was replaced by a Tri-channel Foley's catheter in ICU setup. For both groups, 1st sample of urine were collected just after insertion of catheter and was analyzed in the microbiology laboratory to see any growth of microorganisms (Culture) and their sensitivity pattern of antibiotics (C/S). After getting 1st sample report the subsequent urine sample for C/S was collected on day 3 , 7 , and then weekly till removal of catheter or up to 28th post catheter insertion day, which one come first. CAUTI was diagnosed when the urine culture shows growth of microorganism > 105 CFU/ml of urine.Data was collected according to preformed data collection sheet. The whole data were computed, and statistical analyses were carried out by using the SPSS. The mean values were calculated for continuous variables. The qualitative observations were expressed by frequencies and percentages. Chi-Square test was used to analyze the categorical variables. Unpaired t-test was used for continuous variables. P value